1996
DOI: 10.1111/1523-1747.ep12343791
|View full text |Cite
|
Sign up to set email alerts
|

Interkeratinocyte Adherens Juncitons: Immunocytochemical Visualization of Cell-Cell Junctional Structures, Distinct from Desmosomes, in Human Epidermis

Abstract: Vinculin and beta-catenin are intracellular attachment proteins linking transmembrane adhesion molecules (E-cadherin) to the actin microfilament cytoskeleton, thus participating in formation of cell-cell adherens junctions, or zonulae adherentes. This type of junction was only recently described in human epidermis due to the imprecise morphological criteria for its recognition. In this study, we investigated the relationship between the expression of the zonula adherens-associated proteins vinculin, beta-caten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 30 publications
3
30
0
1
Order By: Relevance
“…In all these tissues, the myozap-containing AJ-type junctions for the most part appear as fasciae adhaerentes of varying lengths, as whiskers, commata or as dots (puncta adhaerentia) but at present AJs encircling entire cells in a zonula-like mode cannot be totally excluded. Whether these myozap-positive AJ structures include the small AJtype epidermal structures (e.g., Haftek et al 1996;Kaiser et al 1993) remains to be examined in detail. Here, a special topological problem in our studies of the myozapcontaining AJs in interdesmosomal regions of stratified epithelia and squamous carcinomas has been the close vicinity of these junctions and the strand-, whisker-or dot-like junctional structures positive for tight junction (TJ) markers such as occludin and some claudins (e.g., claudins 1 and 4; see also Brandner et al 2002;Furuse et al 2002;Langbein et al 2002Langbein et al , 2003 for reviews see also Schlueter et al 2007;Shin et al 2006;van Itallie and Anderson 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In all these tissues, the myozap-containing AJ-type junctions for the most part appear as fasciae adhaerentes of varying lengths, as whiskers, commata or as dots (puncta adhaerentia) but at present AJs encircling entire cells in a zonula-like mode cannot be totally excluded. Whether these myozap-positive AJ structures include the small AJtype epidermal structures (e.g., Haftek et al 1996;Kaiser et al 1993) remains to be examined in detail. Here, a special topological problem in our studies of the myozapcontaining AJs in interdesmosomal regions of stratified epithelia and squamous carcinomas has been the close vicinity of these junctions and the strand-, whisker-or dot-like junctional structures positive for tight junction (TJ) markers such as occludin and some claudins (e.g., claudins 1 and 4; see also Brandner et al 2002;Furuse et al 2002;Langbein et al 2002Langbein et al , 2003 for reviews see also Schlueter et al 2007;Shin et al 2006;van Itallie and Anderson 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In order to exhibit their adhesion activity, cadherins must form complexes with catenins, which are linked to actin microfilaments (Kaiser et al, 1993). ot-catenins, plakoglobin (y-catenin), r-catenins, and vinculin are cytoplasmic plaque proteins (Kaiser et al, 1993;Haftek et al, 1996). Vinculin is a plaque protein characteristic of the ZA.…”
Section: Role In Epithelial Adhesionmentioning
confidence: 99%
“…Vinculin is a plaque protein characteristic of the ZA. Recent research has shown that plakoglobin, previously associated with both DS and ZA, is localized only at DS structures (Haftek et al, 1996). The role of ZA in the epidermis is unclear.…”
Section: Role In Epithelial Adhesionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably lacking on TEM of rabbit EE were structures typical of zonula adherens; these were of importance because of their reported role, along with tight junctions, in establishing the junctional barrier in most epithelia. However, failure to identify zonula adherens on TEM does not exclude their presence, because difficulty distinguishing desmosomes from zonula adherens by TEM has been reported in other stratified squamous epithelium (human epidermis) (14).…”
mentioning
confidence: 99%